Application of supercritical gel drying method on fabrication of mechanically improved and biologically safe three-component scaffold composed of graphene oxide/chitosan/hydroxyapatite and characterization studies - Yilmaz, Pelin; Er, Elif Ozturk; Bakirdere, Sezgin; Ulgen, Kutlu; Ozbek, Belma (ELSEVIER, 2019)
Multicomponent-porous scaffolds have recently gained much attention in bone tissue engineering applications due to their ability to mimic the composite structure of natural bone tissue. In the present study, it was aimed to fabricate biologically safe and mechanically improved three-component scaffolds for bone tissue engineering applications. This is the first original report on the application of supercritical gel drying for the fabrication of three component scaffolds composed of graphene oxide (GO) synthesized by Improved Hummers Method, chitosan (CS) and hydroxyapatite (HAp) derived from eggshells. The phase, morphology, mechanical property and in-vitro biocompatibility of scaffolds were investigated by FTIR, XRD, SEM, TEM, BET, TGA, Universal Instron Mechanical Test System, and MTT testing. For the preparation of scaffolds, GO, CS and HAp solutions were blended at various ratios. Resulting mixtures were molded, frozen, exposed to water-acetone substitution procedure, and dried by supercritical gel drying, respectively. Then, dried scaffolds were subjected to MTT testing for cytotoxicity analysis to examine toxicity effect of GO. Results revealed dose-dependent cytotoxicity effect of GO on MC3T3-E1 cell line. The highest relative cell viability was observed with three-component scaffold composed of GO:1 wt%, CS:39 wt% and HAp:60 wt%. According to characterization studies, this original report demonstrated that scaffold produced with the mentioned procedure had a three-dimensional porous sponge-like structure, highest relative cell viability, and increased mechanical compressive strength compared to other scaffolds fabricated. These properties enable scaffold with combined improvement in biological and mechanical properties to be a promising candidate for application in bone tissue materials. (C) 2019 The Authors. Published by Elsevier B.V. This
Keywords: Hydroxyapatite; Graphene oxide; Chitosan; Three-component scaffold; Supercritical gel drying; Characterization studies; TISSUE ENGINEERING APPLICATIONS; HYDROXYAPATITE SCAFFOLDS; BIODEGRADABLE MATERIALS; OXIDE; BIOCOMPATIBILITY; HYDROGEL; Materials Science; Metallurgy & Metallurgical Engineering